Evaluation of 151-hydroxypurpurin-7-lactone (G2) derivatives, Boron Dipyrromethene (BODIPY) and rosamine analogues as photosensitisers for photodynamic cancer therapy / Lim Siang Hui - Lim, Siang Hui (2014)
Photodynamic therapy (PDT) is a therapeutic strategy that utilises the administration of a photosensitiser along with light irradiation to generate reactive singlet oxygen that destruct pathological lesions. However, the current clinically approved photosensitisers for the treatment of cancer present several limitations such as a lack in ideal photophysical and photochemical properties, poor solubility and adverse effects i.e. prolonged photosensitisation or pain following PDT. Therefore, it is necessary to discover and develop new classes of photosensitiser with more ideal properties. From our earlier data, we had shown that 151-hydroxypurpurin-7-lactone dimethyl ester (G2), a semisynthetic cyclic-tetrapyrrole, was a potent photosensitiser. In this study, aspartyl and lysyl amino acids conjugated G2 analogues were prepared and evaluated with the aim to further improve its PDT efficacies. Also included in this study, were two series of non-tetrapyrrolic photosensitisers: boron difluoride dipyrromethene (BODIPY) and rosamine photosensitisers. Both classes of compounds have many characteristics of an ideal photosensitiser and their syntheses are relatively easy to perform and scale-up. For the G2 analogues, results from the study indicated that conjugation of aspartyl or lysyl amino acids was able to modify its properties including light absorption coefficient, singlet oxygen quantum yield, cellular uptake and intracellular localisation. Both conjugations were able to improve the aqueous solubility but resulted in reduced in vitro PDT potency. Further evaluation showed that G2-aspartyl (G2-Asp) was able to achieve similar potency compared to G2 in terms of vasculature occlusion efficiency in chorioallantoic membrane (CAM) model and tumour growth inhibition in a syngeneic mouse model. Meanwhile for the BODIPYs, in vitro data indicated that BODIPY with iodinated core exhibited potent photo-induced cytotoxicity at sub-micromolar IC50 concentrations. Further studies on a lead BODIPY showed exclusive mitochondria localisation, induction of G2/M-phase cell cycle block and onset of apoptosis. The BODIPY molecules also extensively occluded the vasculature of the CAM model. Conversely for the rosamines, they were found to be minimally photoactive, even though several of the derivatives exhibited potent cytotoxicity (average IC50 < 0.5 μM) which was found to be associated with their ability to compromise mitochondrial membrane potential and to inhibit the oxidative phosphorylation complexes primarily the ATP synthase. Preliminary in vivo studies on 4T1 murine breast cancer-bearing female BALB/c mice indicated that treatment with a lead rosamine in a single dosing of 5 mg/kg or a scheduled dosing of 3 mg/kg once every two day for six times (q2d×6) exhibited only minimal tumour growth delay. In conclusion, G2-Asp given its hydrophilic nature, is a pharmaceutically advantageous candidate to be developed into a clinical photosensitiser as it can be formulated easily for administration. Meanwhile for the non-tetrapyrrolic photosensitisers, BODIPY with an iodinated core structure may have potential as new PDT agents for cancer, while the rosamine analogues may be further developed as mitochondrial targeting agents that either directly kill or deliver cytotoxic drugs to selectively kill cancer cells.